Talent Management Dalam Meningkatkan Kinerja Lembaga KSPPS BMT Mitra Sadaya Cabang Purwakarta - Jalaludin Jalaludin; Heru Komarujaman (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
Adaptation companies to pass talent management need at global era in view of information current and fast change and then continuous.Human resources with new talent for organization is need to achieve organization success/performance. Organization must time increase and energy to repair performance from new talent. Talent will compete do the best for organization when organization will appreciate the job.